Bartonella Species in Wild Rodents and Fleas from Them in Japan - KABEYA, Hidenori; INOUE, Kai; IZUMI, Yasuhito; MORITA, Tatsushi; IMAI, Soichi; MARUYAMA, Soichi (Journal of Veterinary Medical Science, 2011)
The purpose of this study was to assess the role of fleas for transmission of Bartonella species among wild rodents in Japan. Flea samples were collected from wild rodents and examined genetically for Bartonella infection. Bartonella DNA was detected from 16 of 40 (40.0%) flea samples. Sequence analysis demonstrated that 3 of 16 (18.8%) of the Bartonella-positive animals were infested with fleas from which the closely related Bartonella DNA sequence was detected, indicating that the fleas acquired Bartonella from the infested rodents. The DNA was detected in hemolymph, the midgut and the ovary (only in female), indicating that Bartonella might be colonized through the midgut and distributed into the body.